Membrane vesicles from the probiotic Nissle 1917 and gut resident Escherichia coli strains distinctly modulate human dendritic cells and subsequent T cell responses. (October 2019) - Diaz-Garrido, Natalia; Fábrega, María-José; Vera, Rodrigo; Giménez, Rosa; Badia, Josefa; Baldomà, Laura
Graphical abstract: Highlights: Modulation of DCs by beneficial gut bacteria is mediated by secreted vesicles (MVs). Activation of DCs and derived Th responses by microbiota MVs are strain-specific. EcN MVs elicit complex Th/Treg responses compatible with the probiotic effects. Commensal E. coli derived MVs mainly differ in their Th1 and Treg responses. Abstract: Extracellular membrane vesicles (MVs) released by gut microbiota are key players in the communication with the host. The aim of this study was to evaluate the immunomodulatory properties of MVs from the probiotic E. coli Nissle 1917 (EcN) in terms of DC-derived adaptive immune responses and to compare the effects with those elicited by commensal E. coli . The effects of MVs were analysed in monocyte-derived DCs by measuring cytokine expression and the ability of activated-DCs to differentiate CD4+ T cells towards specific effector subsets. EcN MVs derived intricate Th1/Th2/Th17/Th22/Treg responses consistent with the beneficial effects of this probiotic. Th2/Th17/Th22 responses were common to commensal E. coli -derived vesicles but specific differences were observed for Th1 and Treg responses. Since MVs activate DCs in a strain-specific manner, probiotic-derived MVs could be explored as a safe (bacteria-free) strategy to develop new functional food ingredients targeting gut microbiota balance or intestinal inflammation.